Interpreting in Sexual and Reproductive Health Consults With Burma Born Refugees Post Settlement: Insights From an Australian Qualitative Study - Tuteja, Amita; Riggs, Elisha; Sanci, Lena; Mascarenhas, Lester; VanVliet, Di; Sangster, Katrina; McGuinness, Kimberley; Temple-Smith, Meredith (Frontiers in Communication, 2021)
Interpreters work with health care professional to overcome language challenges during sexual and reproductive (SRH) health discussions with people from refugee backgrounds. Disclosures of traumatic refugee journeys and sexual assault combined with refugees’ unfamiliarity with Western health concepts and service provision can increase the interpreting challenges. Published literature provides general guidance on working with interpreters in primary care but few studies focus on interpretation in refugee SRH consults. To address this, we explored the challenges faced by providers of refugee services (PRS) during interpreter mediated SRH consultations with Burma born refugees post settlement in Australia. We used qualitative methodology and interviewed 29 PRS involved with refugees from Burma including general practitioners, nurses, interpreters, bilingual social workers, and administrative staff. The interviews were audio-recorded, transcribed, and subjected to thematic analysis following independent coding by the members of the research team. Key themes were formulated after a consensus discussion. The theme of “interpretation related issues” was identified with six sub-themes including a) privacy and confidentiality b) influence of interpreter’s identity c) gender matching of the interpreter d) family member versus professional interpreters e) telephone versus face to face interpreting f) setting up the consultation room. When faced with these interpretation related challenges in providing SRH services to people from refugee backgrounds, health care providers combine best practice advice, experience-based knowledge and “mundane creativity” to adapt to the needs of the specific patients. The complexity of interpreted SRH consultations in refugee settings needs to be appreciated in making good judgments when choosing the best way to optimize communication. This paper identifies the critical elements which could be incorporated when making such a judgement. Future research should include the experiences of refugee patients to provide a more comprehensive perspective.